Microestrutura, absorção de água e resistência à penetração de cloretos em concretos com substituição de cimento Portland por altos teores de fíler calcário e cinza volante - Silva, Silvane Santos da (2023)
The use of alternative materials such as mineral additions (AM) is being studied, evidenced and expanded within the cement industry, and in the formulation of concrete. This demand is due to the environmental impacts caused by the manufacture of clinker, responsible for a large part of CO2 emissions. The sector has been adapting to new requirements with the use of chemically inert or active AM. Within this scope, the present thesis aimed to develop concretes with high levels of replacement of Portland cement (PC), in binary mixtures of limestone filler (FC) and ternary mixtures of FC and fly ash (CV), in contents of up to 80% by mass. Aiming to produce concretes with reduced environmental impact, but which, at the same time, present an adequate performance, the study of the packing of the constituent particles of the mixtures was carried out and through these, the mechanical performance was evaluated in relation to the axial compression, at the ages of 28 and 91 days, the microstructural properties in pastes through analyzes of XRD, TG/DTG, PIM and SEM, at 91 days of age, still, some of the main properties referring to the durability of the concrete were examined, such as the absorption by capillarity at 91 days of age and chloride penetration by immersion (EPCI) at 7, 14, 28, 91, 180 and 360 days of age. Four mixtures were developed, with FC contents of up to 70% and CV of 10% by mass, with the use of a superplasticizer additive, which allowed the use of a water/binder (w/al) factor of 0.25, with a consistency in the range of 100±20 mm, resulting in resistances to axial compression of the order of 52.0 to 88.5 MPa at 91 days of age, highlighting the performance of the 70FC1 mixture 0CV, as it presented a resistance to axial compression of 52.0 MPa, at 91 days, having only 20% CP in its composition. In relation to the two evaluated durability properties (water absorption and chloride penetration) a sharp increase was observed according to the replacement content. In view of the above, the analyzes showed the possibility of making concrete with high FC levels equal to or above 50%, provided that appropriate measures are used, such as strict production control and the means to which it will be inserted, highlighting the indispensable use of superplasticizer additive.